Tahlîl Al-Akhthâ Al-Imlâiyah Fî Nushûsh Khathâbah Thâlibât Al-Mustawâ Al-Awwal Bi Jâmi’ah Ar-Raayah - Ai Aisyatul Mardiyah; Fahmi Ridha; Mada Wijaya Kusumah (Ukazh: Journal of Arabic Studies, 2020)
تهدف هذه الدراسة إلى معرفة الأخطاء الإملائية في نصوص خطابة الطالبات، ومعرفة العوامل التي تسبب تلك الأخطاء، ومعرفة الحلول لعلاجها. والمنهج الذي سلكتها الباحثة هو المنهج الوصف التحليلي. وكشفت هذه الدراسة على أن الأخطاء الإملائية في نصوص خطابة طالبات المستوى الأول بجامعة الراية يبلغ عددها إلى اثنين وخمسين (52) خطأ: ثمانية (8) أخطاء في كتابة همزة القطع، وعشرة (10) أخطاء في كتابة همزة الوصل، وخمسة (5) أخطاء في كتابة الهمزة المتوسطة، وثلاثة (3) أخطاء في كتابة الهمزة المتطرفة، وسبعة (7) أخطاء في إضافة الصائت الطويل، وأربعة (4) أخطاء في حذف الصائت الطويل وكذا في حذف الألف الفارقة، وخطأين (2) في كتابة الألف اللينة، وتسعة (9) أخطاء في استخدام الحرف. فأما العوامل التي تسبب تلك الأخطاء فهي التدخل اللغوي، واللامبالاة بالقاعدة والتساهل، وعدم التركيز، والاستعجال في الكتابة، وعدم فهم القاعدة، وعدم تصحيح مشرفة الخطابة النص. وأما الحلول المقترحة لعلاجها فهي إلمام المعلمة التقابل اللغوي وتحليل الأخطاء، وتوفير التغذية الراجعة بعد الممارسة على الفور، وتصحيح الأخطاء الشائعة على السبورة، وإكثار التدريبات اللغوية وحث الطالبات على التركيز في الدرس والمذاكرة والتأني في الكتابة. This study aims to know the spelling errors in the texts of public speaking for students of the first-year female students’ speeches, to know the factors that cause these errors, and to sive solutions to treat them. The researcher used an analytical-descriptive approach. This study revealed that the spelling errors contained in the texts were fifty-two i.e: eight errors in writing hamzah qath’iy, ten errors in writing hamzah washl, five errors in writing hamzah mutawassithah, three errors in writing hamzah mutatharrifah, seven errors in adding long vowel, four errors in deleting the long vowel as well as in deleting alif fâriqah, two errors in writing alif layyinah and nine errors of misspelling. As for the factors that cause these errors are linguistic overlap, indifference to the rule, carelessness in writing, lack of understanding of the rule, and failure to correct the honourable oratory text. The suggested solutions to treat those errors are the familiarity of the teacher with the linguistic counterpart, the analysis of errors, the provision of feedback immediately after the practice, the correction of common mistakes on the blackboard, the multiplication of language exercises and the urgency of students to focus in the lesson and careful writing.